Facile Synthesis of Highly Water‐Soluble Lanthanide‐Doped t‐LaVO4 NPs for Antifake Ink and Latent Fingermark Detection. Issue 48 (8th November 2017) - Chen, Cailing; Yu, Ying; Li, Chunguang; Liu, Dan; Huang, He; Liang, Chen; Lou, Yue; Han, Yu; Shi, Zhan; Feng, Shouhua
Abstract: In the information age, it is important to protect the security and integrity of the information. As a result, the fluorescent ink as an antifake technology and the fingermark as an information carrier have aroused great interest. In this work, highly water‐soluble lanthanide (Ln 3+ )‐doped tetragonal phase (t‐) LaVO4 nanoparticles (NPs) are successfully obtained via a simple, fast, and green microwave‐assisted hydrothermal method. The average size of t‐LaVO4 NPs is about 43 nm. The aqueous solutions of Ln 3+ ‐doped t‐LaVO4 exhibit excellent fluorescence properties under ultraviolet light (UV) excitation (t‐LaVO4 :10%Eu is bright red and t‐LaVO4 :0.5%Dy is close to white). Some superb antifake fluorescent patterns are printed using Ln 3+ ‐doped t‐LaVO4 aqueous solution as ink, which indicates the as‐prepared Ln 3+ ‐doped t‐LaVO4 NPs as fluorescent ink can meet the various antifake requirements. Notably, the designed convenient antifake fluorescent codes with improved security could be directly scanned and decoded by a smart phone. What's more, the as‐prepared NPs can be used for the development of latent fingermark on various substrates and the second‐level detail information can be clearly obtained from the magnification of a fingermark. These results indicate that the as‐prepared Ln 3+ ‐doped t‐LaVO4 fluorescent NPs have great potential in security application. Abstract : Highly water‐soluble lanthanide‐doped tetragonal phase (t‐) LaVO4 nanoparticles (NPs) are prepared via a facile environmentally‐friendly microwave‐assisted hydrothermal method. The average size of t‐LaVO4 NPs is about 43 nm. The Ln 3+ ‐doped t‐LaVO4 NPs exhibit excellent fluorescence properties under ultraviolet light (UV) excitation, which can be used in the field of antifake ink and fingermark detection.